Zinc-solubilizing Bacillus spp. in conjunction with chemical fertilizers enhance growth, yield, nutrient content, and zinc biofortification in wheat crop - Yadav, Ramesh Chandra; Sharma, Sushil K.; Varma, Ajit; Singh, Udai B.; Kumar, Adarsh; Bhupenchandra, Ingudam; Rai, Jai P.; Sharma, Pawan K.; Singh, Harsh V. (Frontiers in Microbiology, 2023)
Micronutrient deficiency is a serious health issue in resource-poor human populations worldwide which is responsible for the death of millions of women and under-age children in most developing countries. Zinc malnutrition in middle and lower-class family is rampant when daily calorie intake of staple cereals containing extremely low concentrations of micronutrients, especially Zn and Fe. Looking at the importance of the problem, the present investigation aimed to enhance the growth, yield, nutrient status and biofortification of wheat crop by inoculation of native zinc-solubilizing Bacillus spp. in conjunction with soil–applied fertilizersand zinc phosphate in degraded soil. In this study, 175 bacterial isolates were recovered from the rhizosphere of wheat grown in the eastern parts of the Indo-Gangetic Plain of India. These isolates were further screened for Zn-solubilization potential using sparingly insoluble zinc carbonate, zinc oxide and zinc phosphate as a source of Zn under in vitro conditions. Of 175 bacterial isolates, 42 were found to solubilize either one or two or all the three insoluble Zn compounds and subsequently, these isolates were identified based on 16S rRNA gene sequences. Based on zone halo diameter, solubilization efficiency and amount of solubilized zinc, 6 potential bacterial strains, i.e. Bacillus altitudinis AJW-3, B. subtilis ABW-30, B. megaterium CHW-22, B. licheniformis MJW-38, Brevibacillus borstelensis CHW-2, and B. xiamensis BLW-7 were further shortlisted for pot and field level evaluation in wheat crop. Results of the present investigation clearly indicated that these inoculants not only increase plant growth but also enhanced the yield and yield attributes. Further, bacterial inoculation also enhanced available nutrients and microbial activity in the wheat rhizosphere under pot experiments. It was observed that the application of B. megaterium CHW-22 significantly increased the Zn-content in wheat straw and grains along with other nutrients followed by B. licheniformis MJW-38 as compared to other inoculants. By and large, similar observations were recorded under field conditions. Interestingly, when comparing the nutrient use efficiency of wheat, bacterial inoculants showed their potential in enhancing the NUE in a greater way which was further confirmed by correlation and principal component analyses.